Grammar in everyday talk : building responsive actions - Thompson, Sandra A.; Fox, Barbara A.; Couper-Kuhlen, Elizabeth (Cambridge : Cambridge University Press, 2015)
Drawing on everyday telephone and video interactions, this book surveys how English speakers use grammar to formulate responses in ordinary conversation. The authors show that speakers build their responses in a variety of ways: the responses can be longer or shorter, repetitive or not, and can be uttered with different intonational'melodies'. Focusing on four sequence types: responses to questions ('What time are we leaving?' -'Seven'), responses to informings ('The May Company are sure having a big sale' -'Are they?'), responses to assessments ('Track walking is so boring. Even with headphones' -'It is'), and responses to requests ('Please don't tell Adeline' -'Oh no I won't say anything'), they argue that an interactional approach holds the key to explaining why some types of utterances in English conversation seem to have something'missing' and others seem overly wordy.
Machine generated contents note: 1. Introduction; 2. Responses in information-seeking sequences with'question-word interrogatives'; 3. Responses in informing sequences; 4. Sequences with assessment responses; 5. Responses in request-for-action sequences; 6. Conclusions.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: English language -- Grammar; English language -- Usage; English language -- Intonation; Conversation analysis; Speech acts (Linguistics)